Bank Asset Liability Management Best Practice Yesterday, Today and Tomorrow - Bardaeva, Polina (The Moorad Choudhry Global Banking Series, 2021)
As bankers incorporate more and more complicated and precise calculations and models, a solely mathematical approach will fail to confirm the viability of their business. This book explains how to combine ALM concepts with the emotional intelligence of managers in order to maintain the financial health of a bank, and quickly react to external environment challenges and banks' microclimate changes. ALM embraces not only balance sheet targets setting, instruments and methodologies to achieve the targets, but also the correct and holistic understanding of processes that should be set up in a bank to prove its prudency and compliance with internal and external constraints, requirements and limitations and the ongoing continuity of its operations. Bank Asset Liability Management Best Practice delves into the philosophy of ALM, discusses the interrelation of processes inside the bank, and argues that every little change in one aspect of the bank processes has an impact on its other parts. The author discusses the changing role of ALM and its historical and current concepts, its strengths and weaknesses, and future threats and opportunities.